Bridging Aspirations and Policy: An Analysis of Community Input Absorption from Recess Activities of the Regional People's Representative Council in Bengkulu Province - Dani, Rahiman; Purnawan, Heru (Journal Public Policy, 2025)
This study analyzes the effectiveness of recess activities conducted by members of the Regional People's Representative Council of Bengkulu Province in fostering local democracy and promoting community economic development. The research aims to assess how well community aspirations gathered during recess are translated into actionable programs within the 2018 Revised Regional Government Budget. Employing survey methods and literature review, the study classifies and quantifies the absorption of "Main Ideas"—a formal channel for representing community input—into regional development programs. Findings show that while council members actively collect aspirations and advocate for their inclusion through official reports, plenary discussions, and political lobbying, the actual realization of these inputs remains limited. Of the total proposed Main Ideas, only 44% in the productive economy sector, 60.5% in the infrastructure sector, and 36.9% in the socio-economic sector were implemented. This indicates a gap between aspiration collection and program realization, potentially due to limited coordination, bureaucratic challenges, or resource constraints. The study concludes that improving institutional mechanisms, inter-agency coordination, and monitoring systems is essential to enhance the impact of legislative representation. Future research should adopt a longitudinal approach, broaden sectoral coverage, and explore administrative barriers and public perceptions to provide more comprehensive strategies for optimizing the role of regional legislative institutions in local development.